Phytochemistry and antiradical property of Momordica charantia L. - Semeniuk, Lorena V.; Vonka, Carlos A.; Nuñez, María Beatriz (Revista Productos Naturales, 2022)
Momordica charantia L., is a vine that grows in Argentina in the Mesopotamian and coastal region. The most important empirical uses are anticholesterolemic, hypoglycemic, antianemic, purgative and healing. Our objective was to explore the main metabolites and the antiradical properties of both the liquid extract and the solid formulations with M. charantia.